Research of parameters of the modernized subgrade - Petrenko, V. D.; Alkhdour, A. M. M.; Tiut’kin, A. L.; Kovalevich, V. V. (Science and Transport Progress, 2012)
The article presents the results of analysis of the strained-and-stressed state for subgrade during its modernization.